Tratamento de efluente de aquicultura com macrófitas flutuantes: revisão sistêmica e metanálise - Nogueira, Gabriele dos Santos (2019)
Aquaculture is a production of organisms that shows partial or total development in water, generating a nutrient-rich effluent. The use of artificial foods is common in production, but rich in nutrients such as nitrogen and phosphorus. Those nutrients are sources of energy for aquatic plants, like the macrophytes. The use of macrophytes for nutrient absorption is common in some treatment systems such as wetlands. This study aimed to perform a systematic review and meta-analysis of the efficiency of the use of floating macrophytes for the treatment at aquaculture effluents. The platforms used were “Periódicos Capes”, Scopus and Web of Science. The articles found were collected from author data, year of publication, published scientific journal, species of macrophyte, characteristics evaluated without effluents and place of study. Use media and standard deviations of the works found for statistical analysis, through the standardized mean difference (SMD), method for performing meta-analysis. Only 24 articles were part of the systemic review, including 9 articles that could be extracted as necessary information for the meta-analysis. Among the chemical properties, the pH was more measured, including those present in 21 articles. The most commonly found macrophyte genera were Eichhornia, Pistia, Lemna, Salvinia and Azolla. Only one meta-analysis of orthophosphate shows no statistical difference, while total nitrogen, ammonia, nitrite, nitrate, total nitrogen, inorganic total nitrogen, total phosphorus and orthophosphate are significant. It can be observed that macrophytes have higher affinity for nutrients.